آليات تطبيق القانون الدولي الإنساني في النزاعات المسلحة: دراسة حالة النزاع المسلح في ليبيا عام 2011م - مهندز، إبراهيم مصطفى إبراهيم (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
This study aimed to investigate the fundamental of international humanitarian law, and the mechanisms of its implementation in times of peace and war, as well as the effect of these mechanisms were studied based on the situation of Libya during the period of the revolution in 2011. In addition, the crimes committed in Libya were investigated in order to measure how they violate the international humanitarian law, the Statute of the International Criminal Court. In addition, the study aims to investigate the action of the major powers, the United Nations and the Security Council towards the crisis in Libya at that time. The researcher relied on explored and analysis a number of methodologies approaches that serve this study. First, the historical approach were using, where many historical evidences have been cited, which helps to enrich the research in terms of science. Second, the descriptive approach that helps in describing the events that happened in Libya during 2011. Third, the analytical approach gives many facts and legal texts, whether in international charters or conventions were analyzed. Then, the researcher applied the comparative approach to compare the difference mechanisms for the implementation of international law. Finally, the inductive approach is used to investigate, collect articles law, and international organizations charters. The study concluded that the international community deals with conflict standards towards crimes that violate international humanitarian law according to its interests. It overlooks some states and applies the international law to other states. Also, using the army forces protect the civilian in Libya, but the Gadafi and his government give them chance to do that by ignore the United Nations and international law.